OP0118 Predictors of overall/cardiovascular mortality in patients with early inflammatory polyarthritis; the lipid-paradox?. (23rd January 2014) - Alhusain, A.Z.; Verstappen, S.M.; Lunt, M.; Mirjafari, H.; Bunn, D.; Marshall, T.; Charlton-menys, V.; Durrington, P.; Symmons, D.; Bruce, I.N.
Abstract : Background: Patients with rheumatoid arthritis (RA) have premature mortality and increased risk of cardiovascular morbidity and mortality. Dyslipidemia is a known risk factor for increased risk of cardiovascular diseases in the general population. The association between lipids and RA is complex. A paradoxical association between dyslipidemia and cardiovascular disease in patients with RA has been noted recently. Objectives: The aim of this study was to examine the association between lipids and overall/cardiovascular mortality in patients with early inflammatory polyarthritis (IP). Methods: Patients aged ≥18 years, who had 2 or more swollen joints for more than 4 weeks were recruited by the Norfolk Arthritis Register (NOAR) a primary inception cohort. The patients were recruited from January 2000-December 2010. Patients were followed up untill event (death) or untill the end of the study (total number of person year follow up 7607.8). The cause of death was coded on death certificates according to the ICD-10. A detailed baseline assessment of patients including joint counts (swollen, tender) was performed. Symptom duration, current and previous therapies were recorded. Fasting blood samples were collected and stored for routine assessment of CRP, rheumatoid factor (RF), anti-CCP antibodies (ACPA) and lipid profiles including total and HDL cholesterol, apolipoprotein (Apo-) A1 and B and triglyceride (TG) levels. Cox-proportional hazard survival analysis was used to determine the association between lipid-subtypes and overall/CVD mortality. Results: We recruited 1266 patients with IP. The median (IQR) age and symptom duration at the time of assessment was 58 (47, 68) years and 8 (4.5, 15) months respectively. The cohort included 848 (67%) women, 538 (42.7%) were RF-positive, and 394 (34.5%) were ACPA-positive. The median (IQR) CRP and DAS-28crp were 11 (5.4, 20.8) and 3.68 (2.82, 4.62) respectively. Overall 568 (41.3%) patients fulfilled 1987 ACR criteria for RA. During the period of follow up 100 (7%) patients died (all causes) of which 30% (27) deaths were attributed to CVD. On univariate analysis all cause mortality was associated with; increasing age HR (95%CI); 1.09 (1.07-1.11) per year, hypertension 2.21 (1.47-3.31), RF+ve 1.54 (1.03-2.29), and ACPA+ve 1.81 (1.15-2.86) respectively. Female gender HR (95%CI) 0.52 (0.35-0.77), BMI 0.93 (0.89-0.97) per kg/m 2, TC 0.79 (0.68-0.93) per mmol, LDL 0.73 (0.59-0.89) per mmol, HDL 0.47 (0.27-0.81) per mmol were associated with reduced risk of overall mortality. This remained significant after adjusting for age and gender. Both ApoA-1 and ApoB were associated with reduced risk but did not reach significant level. A similar trend was also observed in association with CVD mortality. Forward stepwise regression analysis indicated that only increasing age and low level of TC were independently associated with increased risk of both all cause and CVD mortality. Conclusions: In patients with IP, lower lipids at baseline were associated with all cause mortality and CVD deaths. Lower cholesterol levels may reflect a higher inflammatory burden but may also be associated with lipid subsets more prone to oxidation. Disclosure of Interest: None Declared